Pelatihan Pembelajaran Berdiferensiasi bagi Guru-Guru SMK YPPP Wonomulyo sebagai Implementasi Kurikulum Merdeka - Ramdani, Ramdani; Eda Lolo Allo; Sakinah Zubair; Jusniar, Jusniar (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
This study aims to determine the training of differentiated learning as an implementation of the independent curriculum at SMK YPPP Wonomulyo. This activity is part of the trauma of community service through training, which aims to improve teacher competence in applying differentiated learning as an implementation of the independent curriculum. The training was conducted offline with 11 participants from various disciplines. This research is qualitative descriptive research. The training was conducted through 3 stages, namely (1) preparation, (2) implementation through presentations, discussions, questions and answers, and analysis of learner characteristics, and (3) evaluation through questionnaires and observations. The questionnaire results showed that implementing training activities had gone well and provided significant benefits for participants, especially regarding material clarity. The training significantly contributes to the professional development of teachers at SMK YPPP Wonomulyo, especially in the application of differentiated learning. By applying more personalised and relevant learning strategies, SMK student motivation and engagement in the learning process are expected to increase.